Mathematical model of optimal distribution of applied problems of safety-critical systemsover the nodes of the information and telecommunication network - Kosenko, V. V. (NTU "KhPI", 2017)
The subject matter of the article is the processes of synthesis of the information and telecommunication network (ITN) for solving applied problems of safety-critical systems (SCS). The goalis to develop a mathematical model for the optimal distribution of applied tasks of safety-critical systems over the ITN nodes. The tasks to be solved are: to formalize the procedure of distribution of applied tasks and SCS software over the ITN nodes; to develop a mathematical model of optimal distribution in order to minimize the cost of network resources; to select an effective algorithm for solving it. The methods used are: alternative-graph approach, mathematical optimization models, methods for solving nonlinear integer programming problems with Boolean variables. The following results were obtained: the task of selecting the ITN optimal structure was formulated according to the alternative-graph model of information processing; in addition to structural characteristics, the requirements for the parameters necessary for performing applied tasks were taken into account while constructing a mathematical model; when minimizing the cost of a computing resource, constraints related to the capabilities for financing the development and operation of the network are taken into account; the costs for organizing additional connections among the network nodes are considered as well. As a result, a mathematical model of distributing SCS applied problems over the ITN environment was obtained in order to minimize the total costs of computing resource, data transmission, network setting and maintenance. This model is a non-linear integer programming problem with Boolean variables. Taking into account the specific nature of the objective function and model constraints with the use of pseudo-Boolean functions, the original task is reduced to a linear form. The obtained model represents the canonical form of the linear optimizing problem of large-dimensional Boolean programming, for which the method of the recession vector is effective. Conclusions. The scientific novelty of the results obtained is as follows: 1) the optimization model of distributing applied tasks over the nodes of the computer network was improved by defining the objective function in order to minimize the costs of both computational and data transmission and the constraints caused by the requirements for the technical and information struct ure of the network; 2) methods for solving the problems of optimizing the ITN structure on the basis of models of nonlinear Boolean programming by transforming the initial task into a linear form and applying the recession vector method was further developed, which makes obtaining a quasi-optimal solution of the problem in the context of large dimension possible.

Предметом вивчення в статті є процеси синтезу інформаційно-телекомунікаційної мережі (ІТМ) для вирішення прикладних завдань систем критичного призначення (СКН). Метоює розробка математичної моделі оптимального розподілу прикладних задач систем критичного призначення по вузлах ІТМ. Завдання: формалізувати процедуру розподілу прикладних задач і програмного забезпечення СКН по вузлах ІТМ; розробити математичну модель оптимального розподілу для мінімізації вартості мережевих ресурсів; вибрати ефективний алгоритм її вирішення. Використовуваними методамиє: альтернативно-графовий підхід, математичні моделі оптимізації, методи розв'язання нелінійних задач цілочисельного програмування з булевими змінними. Отримані такі результати. Згідно альтернативно-графової моделі процесу обробки інформації сформульована задача вибору оптимальної структури ІТМ. При побудові математичної моделі крім структурних характеристик враховані вимоги до параметрів виконання прикладних завдань. При мінімізації витрат обчислювального ресурсу враховуються обмеження, пов'язані з можливостями фінансування розвитку та експлуатації мережі. Враховуються також витрати на організацію додаткових зв'язків між вузлами мережі. В результаті отримана математична модель розподілу прикладних задач СКН в середовищі ІТМ для мінімізації сумарних витрат обчислювального ресурсу, передачі даних, налаштування та обслуговування мережі. Дана модель являє собою нелінійну задачу цілочисельного програмування з булевими змінними. Зурахуванням специфіки цільової функції і обмежень моделі з використанням псевдобулевих функцій вихідна задача приводиться до лінійної формі. Отримана модель являє канонічний вид лінійної оптимізаційної задачі булевого програмування великої розмірності, для вирішення якої ефективним є метод вектора спаду. Висновки. Наукова новизна отриманих результатів полягає в наступному: ми вдосконалили оптимізаційну модель розподілу прикладних задач по вузлах обчислювальної мережі шляхом визначення цільової функції для мінімізації витрат як обчислювальних, так і передачі даних, і обмежень, зумовлених вимогами до технічної та інформаційної структурі мережі; отримали подальший розвиток методи розв'язання задач оптимізації структури ІТМ на основі моделей нелінійного булева програмування шляхом перетворення вихідної задачі в лінійний вид і застосування методу вектора спаду, що дозволяє отримати квазіоптимальні рішення задачі в умовах великої розмірності.
Математична модель оптимального розподілу прикладних задач систем критичного призначення по вузлах інфокомунікаційної мережі
Keywords: information and telecommunication network; applied problems; optimal distribution; cost minimization; nonlinear model; Boolean variables; інформаційні мережі; телекомунікаційні мережі; прикладні завдання; оптимальний розподіл; мінімізація витрат; нелінійна модель; булеві змінні